Invertebrate Gleaning: Forgotten Fisheries. (April 2019) - Furkon,; Nessa, M N; Ambo-Rappe, R
Abstract: Gleaning is important for the food security of many coastal communities, but data and information on these fisheries are extremely limited. Invertebrate gleaning is a popular fishing method in Bulukumba, Indonesia. The gleaners in Bulukumba recognised only one type, general gleaning. During general gleaning (2-4 hours), all species found will be collected. Women (95%) were more dominant than men (5%). The majority of gleaners utilize catch gleaning for food (62%) and a substantial majority for income (38%). A total of 15 species were collected and identified from gleaning catches, with 2.936 individual items. Gastropods were the dominated group (82.31%) followed by bivalves (7.36%), crustaceans (1.22%) and echinoderms (9.12%). Chicoreus brunneus was the dominant species in all gleaning sites except in Sama Bahari village, where the catch was dominated by Canarium urceus . Invertebrate gleaning plays an important role in providing food and income to coastal communities.